"That's where you start to think like, does anyone actually listen to or watch women's sport?" Gender Regimes and Students Experiences on Higher Education Sport Courses. (March 2023) - Velija, Philippa; Phipps, Catherine
In this article we apply theoretical tools from the work of Elias and Connell to critically discuss the ways in which gender relations on Higher Education sport courses are manifested and experienced by students. Drawing on data from an analysis of curriculum, as well as interviews, surveys and workshops with students across a range of sport courses at one university, we explore curriculum design and the ways in which knowledge is presented which both marginalises and compartmentalises issues of gender, as well as presenting knowledge as gender neutral. This article provides a critical understanding of how knowledge about gender and women's sport features and is taught in UK Higher Education sport courses, alongside how students experiences in the classroom to provide an understanding which reinforces existing gender regimes and gender relations.